2021
DOI: 10.1007/978-3-030-68080-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Using H5P Services to Enhance the Student Evaluation Process in Programming Courses at the Universidad Politécnica Salesiana (Guayaquil, Ecuador)

Abstract: This study analyzes the effectiveness of H5P services used to create interactive student evaluations on a Moodle platform. The content evaluated in this study comes from the Universidad Politécnica Salesiana (Guayaquil, Ecuador) Programing Course syllabus. Study participants are first year university students (18-20 years old). The students participate in a learning validation experience through Python Experiential Educational Platform (PEEP), designed for this purpose. A 75% improvement in retention of acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…H5P-based interactive activities have been incorporated in recent years. Studies have shown that they can enhance several of the advantages found in other blended-learning activities, such as positive impacts on student assessment results, increased learner satisfaction, higher motivation and improved student information retention [27][28][29]. According to recent research, students who participated in interactive H5P activities achieved higher scores than those who participated in traditional online activities [15].…”
Section: H5p In Educationmentioning
confidence: 99%
“…H5P-based interactive activities have been incorporated in recent years. Studies have shown that they can enhance several of the advantages found in other blended-learning activities, such as positive impacts on student assessment results, increased learner satisfaction, higher motivation and improved student information retention [27][28][29]. According to recent research, students who participated in interactive H5P activities achieved higher scores than those who participated in traditional online activities [15].…”
Section: H5p In Educationmentioning
confidence: 99%
“…From these plug-ins, Jacob et al [20] affirmed that the incorporation of interactive H5P resources within online educational courses has the potential to foster heightened levels of student engagement. Other authors have also emphasized that H5P has emerged as a pioneering solution for addressing technological and educational challenges [26]. It empowers instructional faculty to design interactive learning experiences by leveraging freely available opensource resources, while also facilitating knowledge exchange and learner engagement through a diverse range of interactive and mobile-friendly learning tools crafted, shared, and reused by educators [40,57].…”
Section: Introductionmentioning
confidence: 99%
“…As a platform to foster independent learning, H5P is actively involved in the learning process (Llerena-Izquierdo & Zamora-Galindo, 2021;Sinnayah et al, 2021). H5P interactive video is a form of learning video that combines interactive technology with web-based learning technology.…”
Section: Introductionmentioning
confidence: 99%